An optimized process for in situ formation of multi-walled carbon nanotubes in templated pores of polymer-derived silicon oxycarbide. Issue 4 (March 2017) - Peng, Yuqing; Wang, Kaishi; Yu, Muhuo; Li, Aijun; Bordia, Rajendra K.
Abstract: A reliable and optimized process to grow carbon nanotubes (CNTs) in templated pores of polymer derived ceramic (PDC) matrix was developed. It is realized through the pyrolysis of a preceramic polymer, i.e., poly (methyl-phenyl-silsesquioxane) (denoted as PMPS), in argon atmosphere at 1000 °C together with nickel-catalyst-coated poly-methyl-methacrylate (PMMA) microbeads (denoted as PMMA-Ni). PMPS served as both a precursor for the ceramic matrix and a carbon source for the CNT growth. PMMA microbeads were used as sacrificial pore formers and coated with nickel via an electroless plating method, which provides an improved control of particle size of the catalyst and its distribution in the material. The influence of PMMA-Ni loading on the in situ growth of CNTs and the properties of CNTs/SiOC nanocomposites were studied through thermogravimetric analysis (TGA), scanning electron microscopy (SEM), X-ray diffraction (XRD), Raman spectroscopy, and density/porosity measurements. Under optimized conditions, uniform distribution of in situ grown CNTs was observed within the templated pores of the SiOC matrix. The optimized process leads to reproducible high yield of CNTs in the pores. The development of such novel CNT/cellular ceramic nanocomposite materials is of significant interest for a variety of sensor applications.